Between Conservation and Edu-Ecotourism: The Strategy of PT Pertamina EP Pangkalan Susu Field for Community-Driven Mangrove Ecosystem Preservation - Putranto, Nurseno Dwi; Ayuni, Rara; Rohim, Abdur; Puspitasari, Novita Indriyani (Global Writing Academica Researching and Publishing, 2024)
The mangrove ecosystem is one of the crucial ecosystems for climate and environmental balance. However, the existence of mangroves is increasingly threatened due to land-use changes, as seen on the Northern East Coast of Sumatra, particularly in the Langkat Regency area. The mangrove areas have been damaged due to illegal logging and gradually transformed into shrimp ponds and palm oil plantations. This situation prompted Pertamina EP Pangkalan Susu Field to initiate community-driven mangrove conservation through the Mangrove Edu-Ecotourism Program in Pasar Rawa. Utilizing a descriptive approach and qualitative data, this paper sought to explain the strategies implemented by Pertamina EP Pangkalan Susu Field in community-driven mangrove conservation and its positive impact on environmental ecosystems and community welfare. The results show that the Mangrove Edu-Ecotourism Program in Pasar Rawa consists of two main aspects. The first is the conservation aspect, demonstrated through activities such as mangrove seedling, planting, and education. The second aspect is community economic enhancement, manifested through the development of edu-ecotourism and MSMEs. Ultimately, the program has succeeded in realizing mangrove preservation and improving the living standards of the coastal communities in Pasar Rawa Village. The community, which was previously indifferent to preserving the mangrove ecosystem, has now become an integral part of its conservation efforts.